2021 EU internet refferal unit transparency report: terrorist propaganda monitoring and analysis, referrals, and public-private partnerships (Publications Office of the European Union, 2022)
The report is a factual snapshot of the EU IRU’s activities in 2021, which aim to keep online spaces safe. This includes the sum of the Unit’s activities aiming at reducing public accessibility to online propaganda produced by terrorist organisations.